1979
DOI: 10.1136/vr.105.11.252
|View full text |Cite
|
Sign up to set email alerts
|

The failure of trichothecene mycotoxins and whole cultures of Fusarium tricinctum to cause experimental haemorrhagic syndromes in calves and pigs

Abstract: Piglets and calves were dosed orally with pure diacetoxyscirpenol (DAS) and T-2 toxin, crude extracts of Fusarium tricinctum containing T-2 toxin, and whole cultures of F tricinctum containing T-2 toxin at a constant daily rate of 0.1 mg toxin per kg body-weight (piglets) or 0.2 mg toxin per kg body-weight (calves). The treatment continued for periods of seven to 78 days but it failed to induce clinical haemorrhagic syndromes. Increasing the dose of F tricinctum culture five-fold for eight days following 78 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1983
1983
1986
1986

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Huff et al (1981) reported that large doses of deoxynivalenol administered to day old chicks via oral intubation caused extensive ecchymotic hemorrhaging throughout the body along with other symptoms consistent with the description of hemorrhagic anemia snydrome in chickens caused by moldy feed (Forgacs and Carll 1962). Other workers, however, have reported that oral administration of large doses (0.1-0.6 mg/kg) of purified T-2 toxin or diacetoxyscirpenol to cows, calves or pigs failed to induce any evidence of hemorrhagic syndrome (Matthews et al 1977(Matthews et al , 1979Weaver et al 1980). This failure to obtain hemorrhaging probably does not eliminate the trichothecenes from the etiology of the hemorrhagic syndrome but rather indicates that the syndrome is of a far more complicated nature than having a single cause.…”
Section: Hemorrhagic Syndromementioning
confidence: 66%
See 4 more Smart Citations
“…Huff et al (1981) reported that large doses of deoxynivalenol administered to day old chicks via oral intubation caused extensive ecchymotic hemorrhaging throughout the body along with other symptoms consistent with the description of hemorrhagic anemia snydrome in chickens caused by moldy feed (Forgacs and Carll 1962). Other workers, however, have reported that oral administration of large doses (0.1-0.6 mg/kg) of purified T-2 toxin or diacetoxyscirpenol to cows, calves or pigs failed to induce any evidence of hemorrhagic syndrome (Matthews et al 1977(Matthews et al , 1979Weaver et al 1980). This failure to obtain hemorrhaging probably does not eliminate the trichothecenes from the etiology of the hemorrhagic syndrome but rather indicates that the syndrome is of a far more complicated nature than having a single cause.…”
Section: Hemorrhagic Syndromementioning
confidence: 66%
“…Other workers, however, have reported that oral administration of large doses (0.1-0.6 mg/kg) of purified T-2 toxin or diacetoxyscirpenol to cows, calves or pigs failed to induce any evidence of hemorrhagic syndrome (Matthews et al 1977(Matthews et al , 1979Weaver et al 1980). The slight increase in prothrombin and partial thromboplastin times observed in T-2 toxin treated animals (Patterson et al 1979), probably arise through partial inhibition of liver protein synthesis, and may also make the animals more prone to hemorrphage. The extravization of plasma proteins and red cells from capillaries observed following fusarenon-X treatment of rats indicates the potential for hemorrhage, but other dietary factors almost certainly are involved.…”
Section: Hemorrhagic Syndromementioning
confidence: 98%
See 3 more Smart Citations